Global imbalances from the flow and stock perspective - Knap, Renata (Journal of Management and Financial Sciences, 2020)
The objective of the paper is to identify global payment imbalances from the flow and stock perspective in the years of 2000-2017 as well as to define the causes of differences in the development of global imbalances in both of the analysed aspects. In order to achieve the objective, current account balances and international investment positions that are systemically significant to economies were analysed with the use of descriptive statistics techniques and specific analytical indicators. From the conducted studies it arises that after the outbreak of the global financial crisis, the global flow imbalance declined, whereas the global stock imbalance rose significantly. The demonstrated divergence was caused by insufficient changes in current account balances (flow imbalances) in order to cause a decrease in net international investment positions (stock imbalances) systematically significant to economies and by a weakened impact of the transactions registered in the balance of payment (flows) on the change of an international investment position (stock).